Integritas Diri Tokoh Utama Pada Film â€œThe Ron Clark Storyâ€ Karya Randa Haines - Tuti Apriani; Zainal Rafli; Zuriyati Zuriyati (Jurusan Tadris Bahasa Indonesia, 2019)
This research examines and analyzes the integrity of the main characters in the film The Ron Clark Story by Randa Haines through the depiction of the basic dimensions of man. The film Ron Clark Story tells of a teacher named Ron Clark, he is a teacher who excels. However, because he wanted to have new experiences he moved to the big city of New York. Clark is a figure who has self-integrity, despite many obstacles and obstacles in realizing self-integrity. The self-integrity of Ron Clark's character is examined through the depiction of basic human dimensions which consist of: physical dimensions, psychological dimensions, and social dimensions.Â Penelitian ini bertujuan untuk mengkaji dan menganalisis integritas diri tokoh utama pada film The Ron Clark Story Karya Randa Haines melalui penggambaran dimensi dasar manusia. Film The Ron Clark Story menceritakan tentang seorang guru bernama Ron Clark, dia merupakan guru yang berprestasi. Akan tetapi, karena ingin mempunyai pengalaman baru dia pindah ke kota besar New York. Clark merupakan tokoh yang mempunyai integritas diri, walaupun banyak halangan dan hambatan dalam mewujudkan integritas diri. Integritas diri tokoh Ron Clark dikaji melalui penggambaran dimensi dasar manusia yang terdiri atas: dimensi fisik, dimensi psikis, dan dimensi sosial.